Association of renal biomarkers with fast progressor phenotype and related outcomes in anterior circulation large vessel occlusion stroke - Rios Rocha, Lucas; Kayyali, Mohammad N.; Mahat, Bishow C.; Al-Qudah, Abdullah; Doheim, Mohamed F.; Al-Bayati, Alhamza R.; Bhatt, Nirav R.; Starr, Matthew T.; Song, Shlee S.; Nogueira, Raul G.; Rocha, Marcelo (Frontiers in Neurology, 2024)
BackgroundRenal dysfunction is a known predictor of long-term functional dependency after anterior circulation large vessel occlusion (ACLVO) stroke. However, the impact of renal dysfunction on early infarct growth rate (IGR) has not been previously demonstrated. The objective of this study was to define the association of creatinine-based renal biomarkers with fast or slow progressor phenotypes and related clinical outcomes in ACLVO stroke.MethodsThis retrospective study examined patients with acute intracranial internal carotid artery or middle cerebral artery-M1 occlusions admitted between 2014 and 2019. Patients were included if they received baseline CT perfusion (CTP) or MRI on presentation within 24 h of estimated stroke onset. Infarct growth rate (IGR) was determined by ischemic core volume on CTP or MRI divided by time from stroke onset to imaging. IGR was used to stratify fast progressor (IGR ≥10 mL/h) and slow progressor (IGR < 10 mL/h) status. Renal dysfunction was assessed based on serum creatinine and estimated glomerular filtration rate (eGFR) on presenting laboratories. Logistic regression models, adjusted for significant covariates, identified independent associations between renal dysfunction biomarkers, progressor status, and clinical outcomes based on modified Rankin Scale (mRS) at 90 days.ResultsAmong 230 patients with ACLVO, 29% were fast progressors, with median serum creatinine levels higher than slow progressors (1.1 vs. 0.9 mg/dL, p < 0.05) and lower median eGFR (66.2 vs. 69.0 mL/min/1.73m2, p < 0.05). Elevated creatinine (≥1.2 mg/dL) was independently associated with fast progressor status (adjusted OR 2.37, 95% CI 1.18–4.77), worse 90-day mRS (adjusted OR 1.88, 95% CI 1.01–3.51) and mortality (adjusted OR 2.57, 95% CI 1.14–5.79). Reduced eGFR (<60 mL/min/1.73m2) was independently associated with fast progressor status (adjusted OR 2.38, 95% CI 1.14–4.94), but not with 90-day mRS or mortality.ConclusionSerum creatinine-based biomarkers of renal dysfunction were associated with fast progressor phenotype of ACLVO stroke, and worse clinical outcomes, which may help identify such patients earlier during emergency evaluation for expedited access to EVT. Future prospective studies are warranted to confirm and test implementation of these findings.